2023
DOI: 10.3389/fphar.2023.1100488
|View full text |Cite
|
Sign up to set email alerts
|

Clofazimine for the treatment of tuberculosis

Abstract: Shorter (6–9 months), fully oral regimens containing new and repurposed drugs are now the first-choice option for the treatment of drug-resistant tuberculosis (DR-TB). Clofazimine, long used in the treatment of leprosy, is one such repurposed drug that has become a cornerstone of DR-TB treatment and ongoing trials are exploring novel, shorter clofazimine-containing regimens for drug-resistant as well as drug-susceptible tuberculosis. Clofazimine’s repurposing was informed by evidence of potent activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 159 publications
1
22
0
Order By: Relevance
“…It has been altered for the treatment of drug-resistant TB. In preclinical and clinical trials, it has been shown that adding clofazimine to treatment regimens for MDR-TB and XDR-TB improves treatment outcomes and decreases the time to culture conversion …”
Section: Emerging Antimicrobial Agents Against Mycobacterium Tubercul...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been altered for the treatment of drug-resistant TB. In preclinical and clinical trials, it has been shown that adding clofazimine to treatment regimens for MDR-TB and XDR-TB improves treatment outcomes and decreases the time to culture conversion …”
Section: Emerging Antimicrobial Agents Against Mycobacterium Tubercul...mentioning
confidence: 99%
“…It has been altered for the treatment of drug-resistant TB. In preclinical and clinical trials, it has been shown that adding clofazimine to treatment regimens for MDR-TB and XDR-TB improves treatment outcomes and decreases the time to culture conversion Nitazoxanide: An antiparasitic drug, nitazoxanide has shown encouraging antimycobacterial activity against M. tuberculosis .…”
Section: Emerging Antimicrobial Agents Against Mycobacterium Tubercul...mentioning
confidence: 99%
“…Typical phenazines such as phenazine-1-carboxylic acid (PCA) and phenazine-1-carboxamide (PCN) are promising biopesticides for agricultural diseases while some more highly substituted phenazines display anticancer and radical scavenging properties . Besides, clofazimine is a clinically used antileprotic and antitubercular phenazine drug . Phenazines can also be adopted as components of microbial fuel cells and environmental sensors .…”
Section: Introductionmentioning
confidence: 99%
“…1 Besides, clofazimine is a clinically used antileprotic and antitubercular phenazine drug. 4 Phenazines can also be adopted as components of microbial fuel cells 5 and environmental sensors. 6 Accordingly, the identification and efficient production of phenazines are of great interest.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Selected examples of compounds that exhibit cross-phylum/multikingdom activity against phylogenetically diverse pathogens include nitazoxanide (thiazolide class used to treat Apicomplexa and Metamonada pathogens), paromomycin (amino cyclitol glycoside used to treat Amoebozoa, Euglenozoa, Metamonada, and Platyhelminthes pathogens), and tinidazole (nitroimidazole class used to treat Amoebozoa, Campylobacterota, and Metamonada pathogens) . These and other emerging agents illustrate the scope of opportunities that exist pertaining to the identification, development, and employment of broad-spectrum anti-infectives …”
mentioning
confidence: 99%